Comparison of Major External Actors` Strategies for the Power Sector Development in Sub-Saharan Africa - K. A. Gemueva (Сравнительная политика)
In order to promote industrialization and improve the living standards of the population in the Sub-Saharan countries, large-scale investments in power infrastructure development are required. Two key and two secondary long-term objectives for the energy sector development can be distinguished. The first ones are to enable industrial development and to increase its competitiveness, as well as to promote socio-economic development by ensuring universal access to electricity and uninterrupted supply. The latter two are to increase financial sustainability of the energy sector and to meet environmental requirements. Due to lack of financial resources, necessary technologies and professional staff in the Sub-Saharan countries, external players play a crucial role in the power sector development. These external actors include traditional donors such as the World Bank, the EU, the US and the African Development Bank, and new players like China. The purpose of this study is to compare the strategies of key external players in the power sector of the Sub-Saharan countries. The analysis of strategies is carried out at the level of the conceptual framework of the foreign policies toward Africa in general and the power sector development strategies in particular, and at the level of their actual implementation by studying the methods used, priority areas, scale and features of projects. Based on the review, the author provides an assessment of whether the strategies of major external actors for the power sector development serve the vital interests of the Sub-Saharan countries. In conclusion, the author identifies two types of tentative conceptually distinct models, i.e. “equal partnership” and “donor ‒ recipient” strategies.